2013
DOI: 10.3171/2013.7.jns13217
|View full text |Cite
|
Sign up to set email alerts
|

Results of Gamma Knife surgery for Cushing's disease

Abstract: Gamma Knife surgery offers a high rate of tumor control and a reasonable rate of endocrine remission in patients with Cushing's disease. The cessation of cortisol-lowering medications around the time of GKS appears to result in a more rapid rate of remission. Delayed hypopituitarism and endocrine recurrence develop in a minority of patients and underscore the need for long-term multidisciplinary follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
70
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(79 citation statements)
references
References 44 publications
5
70
0
4
Order By: Relevance
“…Considering the studies on GK, in a follow-up period of 2-264 months (mean, 48.9 mo; median, 46.1 mo), the remission rate was 10 -100% (mean, 58.7%; median, 55.6%) (318 -321, 323-334, 336, 337, 339 -347). The time to remission is nonhomogeneously expressed in the different studies, being reported as a range (1-166 mo) in 10 studies (318, 327-329, 331, 334, 342-344, 346), as a mean (3-58.3 mo) in 11 studies (323, 327-329, 332, 336, 337, 342-344, 347) and as a median (14 -45 mo) in five studies (329,334,341,342,346). In these series, the recurrence rate was 0 -100%, with mean and median re- (322,335,338,339,349).…”
Section: Efficacy Of Pituitary Radiotherapymentioning
confidence: 96%
“…Considering the studies on GK, in a follow-up period of 2-264 months (mean, 48.9 mo; median, 46.1 mo), the remission rate was 10 -100% (mean, 58.7%; median, 55.6%) (318 -321, 323-334, 336, 337, 339 -347). The time to remission is nonhomogeneously expressed in the different studies, being reported as a range (1-166 mo) in 10 studies (318, 327-329, 331, 334, 342-344, 346), as a mean (3-58.3 mo) in 11 studies (323, 327-329, 332, 336, 337, 342-344, 347) and as a median (14 -45 mo) in five studies (329,334,341,342,346). In these series, the recurrence rate was 0 -100%, with mean and median re- (322,335,338,339,349).…”
Section: Efficacy Of Pituitary Radiotherapymentioning
confidence: 96%
“…The optimal dose is 20-25 Gy for SRS and 45-50.4 Gy given over 5 weeks for radiation therapy. 85,98 Generally, the incidence of remission in CD seems to be similar between the various forms of radiosurgery (43%-58%) and fractionated therapies (46%-84%; Table 3), 13,30,85,94,98,108,109 but the pace of the therapeutic response may be faster with SRS. The major risk of SRS or fractionated irradiation therapy is loss of pituitary function, which is presumably the net effect of surgery and radiation.…”
Section: Radiation Therapymentioning
confidence: 99%
“…In a another study conducted in 2013,stereotactic radiosurgery was performed in patients with persistent Cushing's disease after prior resection. Tumour control was achieved in 98% patients and new loss of pituitary function occurred in 36% patients [8].…”
Section: Discussionmentioning
confidence: 97%